Cancer and Exercise: Warburg Hypothesis, Tumour Metabolism and High-Intensity Anaerobic Exercise - Peter Hofmann (MDPI AG, 2018)
There is ample evidence that regular moderate to vigorous aerobic physical activity is related to a reduced risk for various forms of cancer to suggest a causal relationship. Exercise is associated with positive changes in fitness, body composition, and physical functioning as well as in patient-reported outcomes such as fatigue, sleep quality, or health-related quality of life. Emerging evidence indicates that exercise may also be directly linked to the control of tumour biology through direct effects on tumour-intrinsic factors. Beside a multitude of effects of exercise on the human body, one underscored effect of exercise training is to target the specific metabolism of tumour cells, namely the Warburg-type highly glycolytic metabolism. Tumour metabolism as well as the tumour-host interaction may be selectively influenced by single bouts as well as regularly applied exercise, dependent on exercise intensity, duration, frequency and mode. High-intensity anaerobic exercise was shown to inhibit glycolysis and some studies in animals showed that effects on tumour growth might be stronger compared with moderate-intensity aerobic exercise. High-intensity exercise was shown to be safe in patients; however, it has to be applied carefully with an individualized prescription of exercise.